A Simple Electronic Circuit for an Automatic Train Safety Stop System - Donza, A.; Jones, R.; Teixeira, R.; da Silva, B. (Engineering, Technology & Applied Science Research, 2018)
A particular safety system known as “dead man’s circuit” detects the presence of human command in the conduction of the trains operated by the Brazilian Company of Urban Trains (CBTU) in Recife, Brazil, thus consisting a security mechanism that makes automatic braking of any train composition circulating in the transportation system of the city feasible in incidents of loss or apparent loss of driving. Originally, the electrical signal indicating human control in the conduction of the vehicles came from the descent of the traction lever in the driving cabins, which caused the switching of a pair of electrical contacts. Given the importance of the system and the need to avoid repetitive strain injuries to drivers, the need to push the traction knob was eliminated by the use of an electronic device developed by an outsourced company and deployed in the trains of the older fleet. However, the high failure and downtime rates associated with the circuit acquired from the referred contracted company, caused the need to develop a more robust and maintenance-friendly design for the dead man’s system. In fact, despite the good performance of the purchased system, the strength of the resin coating that accommodated the capacitive touch sensor assembly at the end of the traction lever prevented the corresponding electronic circuit from any access for research or corrective interventions. Thus, the content of this paper essentially presents the specifications and the description of operation of the alternative electronic circuit designed for the dead man’s system, which is operating normally without electrical defects in 4 old trains for almost a year..